h - Bhattacharyya, Krishnachandra, 1875-1949. (New Delhi ; Oxford : Oxford University Press, 2011)
This book is the first English translation of the classic philosophical treatise Kantadarsaner Tatparyya. Bhattacharyya combines the basic tenets of Kant to present it in terms of Indian philosophical traditions. The introduction discusses the need for the translation, the challenges involved, and the context.
Includes bibliographical references and index.
Translated from the Bengali.
Description based on print version record.
Keywords: Kant, Immanuel, -- 1724-1804.